Endodontic management of a foreign body - Satish R Kalyan; Girija Sajjan (Wolters Kluwer Medknow Publications, 2010)
The discovery of a foreign object embedded in a tooth is relatively uncommon. Some people have a habit of placing foreign objects to remove food plugs from the teeth. However, occasionally, these objects may be lodged in the teeth. These foreign objects may act as a potential source of infection and may later lead to a painful condition. A detailed case history, clinical, and radiographic examination is required to ascertain the size, position, and likely composition of the object, and also difficulty involved in its retrieval. This paper describes the successful retrieval of stapler pin located in the apical portion of root canal by simple orthograde nonsurgical technique.